Field evaluation of improved cowpea lines for resistance to bacterial blight, virus and striga under natural infestation in the West African savannas - Ajeigbe, Hakeem A.; Singh, B.B.; Emechebe, A.M. (2008)
The average productivity of cowpea in the existing traditional systems is low due to a complex of biotic and abiotic stresses. The biotic factors include insect pests, parasitic plants, and viral, fungal and bacterial diseases. Concerted efforts are being made to develop improved cowpea varieties with combined resistance to these constraints. Twenty five cowpea lines including two local land-races were grown at three locations in the first year (2002) and at six locations in the second year (2003) in Nigeria and Niger for field screening for resistance to Bacterial blight. Many of the improved varieties had significantly higher grain and fodder yields than the local checks. There was genotype x environment interactions for grain and fodder yields. About 44% of the varieties tested were resistant to bacterial blight while 20% showed moderate resistance and others were susceptible. Bacterial blight was more important in the Sahel, and several improved cowpea breeding lines, IT98K-506-1, IT97K-1113-7, IT97K- 1069-6, IT97K-1092-2, IT97K-1069-5, IT98K-131-2 and IT97K-568-18 produced higher grain and fodder yields than the other varieties and showed combined resistance to the disease. These varieties should therefore be evaluated on-farm for onward release to farmers where there seed types meet the farmers preferred seed type other wise they can be used as parent lines as source of important genes for resistant to the diseases and high grain and fodder yields.